Pyrochlore Compounds From Atomistic Simulations - Connor, Timothy; Cheong, Oskar; Bornhake, Thomas; Shad, Alison C.; Tesch, Rebekka; Sun, Mengli; He, Zhengda; Bukayemsky, Andrey; Vinograd, Victor L.; Finkeldei, Sarah C.; Kowalski, Piotr M. (Frontiers in Chemistry, 2021)
Pyrochlore compounds (A2B2O7) have a large applicability in various branches of science and technology. These materials are considered for use as effective ionic conductors for solid state batteries or as matrices for immobilization of actinide elements, amongst many other applications. In this contribution we discuss the simulation-based effort made in the Institute of Energy and Climate Research at Forschungszentrum Jülich and partner institutions regarding reliable computation of properties of pyrochlore and defect fluorite compounds. In the scope of this contribution, we focus on the investigation of dopant incorporation, defect formation and anion migration, as well as understanding of order-disorder transitions in these compounds. We present new, accurate simulated data on incorporation of U, Np, Pu, Am and Cm actinide elements into pyrochlores, activation energies for oxygen migration and radiation damage-induced structural changes in these materials. All the discussed simulation results are combined with available experimental data to provide a reliable description of properties of investigated materials. We demonstrate that a synergy of computed and experimental data leads to a superior characterization of pyrochlores, which could not be easily achieved by either of these methods when applied separately.